Disposition and Critical Thinking Skills: Accounting Students Perspective - Setiaji, Yongky Teguh; Suryani, Ani Wilujeng; Novia, Sanny Sheilla; Pamungkas, Salsabila Putri; Rizqi, Iqbal Ainur (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2026)
Critical Thinking Skills (CTS) is an important element in the 21st century skills accounting students must have. Learning characteristics that are technical and procedural limit students to have CTS, and hence, a habit (disposition) is required to foster CTS. This study aims to determine the influence of critical thinking disposition on accounting students' CTS. We collected survey responses from 361 accounting students. The results showed that critical thinking disposition has a positive effect on CTS. There is no difference in the level of ability between men and women on the variables. Educators should be able to deliver learning process that improves students' CTS through critical thinking disposition, such as problem-based, case study, project-based, and collaborative learning.